Attitudes and practices associated with pubic hair grooming behaviours: A cross‐sectional study. (18th December 2022) - Deans, Rebecca; Cui, Cathy Kexin; Tam, Catherine; Coronel, Ana Beatrice L.; Rosa, Gabriela; Gerstl, Brigitte
Abstract : Background: Female pubic hair grooming (PHG) habits have changed in the last 20 years. Most studies present findings around female PHG attitudes, practices, and behaviours, lacking data on male attitudes and practices. Aims: We explored the attitudes and practices of PHG from male and female perspectives. Materials and Methods: A cross‐sectional convenience survey was conducted online with 1560 male and female young adult participants aged 18 to 25 years. The study was conducted over two time periods (2014 and 2021). The survey explored attitudes, practices, and behaviours around PHG. Descriptive statistics included frequencies and proportions for categorical variables and the median for continuous variables. Males and females were compared using the χ 2 test or Fisher's exact test for categorical variables. We used logistic regression to explore independent factors of PHG. Results: Seventy‐two percent ( n  = 471/728) of females and 64.7% ( n  = 257/728) of males were likely to engage in PHG. Participants were more likely to groom their pubic hair for reasons associated with religion (adjusted odds ratio (aOR): 9.01, 95% CI: 2.87–28.2), comfort when wearing clothing (aOR: 3.85, 95% CI: 1.52–9.71), a neater and cleaner genital appearance (aOR: 3.90, 95% CI: 1.62–9.41) and before attending a healthcare consultation (aOR: 4.79, 95% CI: 2.27–10.09). Moreover, twice as many females compared with male groomers reported watching pornography (69.7% vs 30.3%). Conclusion: Several factors can influence PHG. Our findings demonstrate that the reasons participants engage in PHG practices are for hygiene, aesthetics, comfort, and sexual satisfaction.